Stabilization of expansive black cotton soil using bioenzymes produced by ureolytic bacteria - Eshetu Mekonnen; Yared Amdie; Habtamu Etefa; Nurelign Tefera; Mesfin Tafesse (International Journal of Geo-Engineering, 2022)
Abstract Soil stabilization is the art and science of improving the engineering properties of soils. The properties of problematic soils can be improved by blending appropriate amount of insitu soil, aggregates and bioenzymes. In the present study, four bacterial strains: Sporosarcina pasteurii, Bacillus paramycoides, Citrobacter sedlakii, and Enterobacter bugadensis were used to produce bioenzymes using urea supplemented molasses as a substrate via submerged fermentation. The crude bioenzyme was mixed with modified soil blended with 40% black cotton soil, 30% aggregate and 30% river sand; then tested after curing for 7 days. The test results revealed that except soil samples treated with bioenzyme of Enterobacter bugadensis, all treated soil samples showed improved plasticity index (18–55%) and liquid limit (5–44%). Soil samples treated with bioenzyme of Bacillus paramycoides, Citrobacter sedlakii and Sporosarcina pasteurii showed higher CBR values of 12.9%, 12.27%, and 11.95% respectively. On the other hand, free swell showed reduction in soil samples treated with bioenzymes of Sporosarcina pasteurii (47.37%), Bacillus paramycoides (30%), and Citrobacter sedlakii (10.53%). The highest percentage improvement of linear shrinkage was recorded for soil sample treated with bioenzymes of Sporosarcina pasteuri (39.65%), followed by Permazyme (10.44%), Citrobacter sedlakii (8.4%) and Bacillus paramycoides (8.34%). Whereas, the highest percentage improvement in MDD was recorded in permazyme treated soil (11.92%) followed by molasses (8.29%), Bacillus paramycoides (1.92%), and Enterobacter bugadensis (0.73%). The lowest optimum moisture content (9.3%) was recorded in soil treated with permazyme. Triaxial test analysis also showed improvement in both cohesion and angle of friction in bioenzyme treated soils. From the test results it was concluded that it is possible to treat expansive black cotton soils using bioenzymes produced from low cost substrates such as molasses and reduce the cost of construction and environmental carbon emission.